1998
DOI: 10.1128/jvi.72.7.6169-6174.1998
|View full text |Cite
|
Sign up to set email alerts
|

Role of Individual T-Cell Epitopes of Theiler’s Virus in the Pathogenesis of Demyelination Correlates with the Ability To Induce a Th1 Response

Abstract: Intracerebral inoculation of susceptible strains of mice with Theiler’s murine encephalomyelitis virus (TMEV) results in immune-mediated demyelination. Three major T-cell epitopes have previously been identified within the VP1 (VP1233–250), VP2 (VP274–86), and VP3 (VP324–37) capsid proteins in virus-infected SJL/J mice. These epitopes appear to account for the majority (∼90%) of major histocompatibility complex class II-restricted T-cell responses to TMEV. Interestingly, the effect of immunization with synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Six predominant linear antibody epitope areas, ranging from 13-26 amino acid residues were identified with antibodies from virus-infected mice (17; Fig. 1): A1A (VP1 [12][13][14][15][16][17][18][19][20][21][22][23][24][25] ),A1B (VP1 146-160 ),A1C (VP1 262-276 ), A2A (VP2 2-16 ), A2B (VP2 165-179 ), and A3A (VP3 [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. A time course study indicated that susceptible SJL mice intracerebrally infected with TMEV strongly and selectively recognize the A1C epitope of VP1 as compared to resistant BALB/c or C57BL/6 mice.…”
Section: Antibody Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Six predominant linear antibody epitope areas, ranging from 13-26 amino acid residues were identified with antibodies from virus-infected mice (17; Fig. 1): A1A (VP1 [12][13][14][15][16][17][18][19][20][21][22][23][24][25] ),A1B (VP1 146-160 ),A1C (VP1 262-276 ), A2A (VP2 2-16 ), A2B (VP2 165-179 ), and A3A (VP3 [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. A time course study indicated that susceptible SJL mice intracerebrally infected with TMEV strongly and selectively recognize the A1C epitope of VP1 as compared to resistant BALB/c or C57BL/6 mice.…”
Section: Antibody Responsementioning
confidence: 99%
“…The development and progression of demyelinating disease correlate well with the level of Th1 responses specific for viral epitopes (30)(31)(32). Administration of bacterial lipopolysaccharide (LPS) or IL-1β potentiating inflammatory Th1 responses into genetically resistant C57BL/6 mice infected with TMEV resulted in clinical symptoms (33).…”
Section: Cd4 + T Cell Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research has attempted to ascertain whether CD4 C or CD8 C T cells are involved in the initiation, progression and/or regulation of TMEV-IDD. The evidence for CD4 C T cells as mediators of TMEV pathology in susceptible SJL mice is signicant in that: 1) monoclonal antibodies against CD4, MHC Class II, or IL-12 either prevented or diminished clinical signs (Friedmann et al, 1987;Welsh et al, 1987;Inoue et al, 1998); 2) ow cytometric and histological data from infected SJL/J mice revealed an increased level of CD4 C T cells and their proin ammatory cytokines during clinical disease progression, and transfer of a CD4 C VP2-speci c T cell line leads to increased incidence and accelerated onset of disease (Gerety et al, 1994;Pope et al, 1996;Begolka et al, 1998); 3) the development of virus and myelin antigen-speci c DTH corresponds with onset and chronicity of demyelination (Clatch et al, 1986;Miller et al, 1997); 4) epitopes of TMEV that elicit a Th1 response and DTH can accelerate the pathogenesis of TMEV upon active immunization (Yauch et al, 1998); and 5) tolerance via ECDI-coupled cells with TMEV, known to reduce IL-2 and IFN-°from Th1 cells, reduces the severity of disease (Peterson et al, 1993;Karpus et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of host with either anti-thymocyte, anti-Ia (MHC class II), or anti-CD4 antibodies delays the onset of disease (15)(16)(17), suggesting the involvement of CD4 + T cells. T helper type 1 (Th1) cells preferentially producing interferon-γ (IFN-γ) are found within demyelinating lesions of the CNS and appear to be involved in the pathogenesis of demyelination (18)(19)(20)(21). Furthermore, the genetic association between susceptibility to TMEV-IDD and the major histocompatibility complex (MHC) (22,23), as well as the T-cell receptor (TCR) βchain (24,25), further supports the involvement of such immune responses in pathogenesis.…”
Section: Introductionmentioning
confidence: 99%